The hippocampus participates in the control of locomotion speed. (17th December 2015) - López Ruiz, J.R.; Osuna Carrasco, L.P.; López Valenzuela, C.L.; Franco Rodríguez, N.E.; de la Torre Valdovinos, B.; Jiménez Estrada, I.; Dueñas Jiménez, J.M.; Dueñas Jiménez, S.H.
Highlights: A penetrating injury in CA1 interrupts the hippocampus – locomotor system circuit. A penetrating injury in the hippocampus augments the stride speed. Tamoxifen restores the stride speed at 7 days post injury. Tamoxifen preserves the neurons after the penetrating injury in the hippocampus. Abstract: The hippocampus role in sensory-motor integration remains unclear. In these experiments we study its function in the locomotor control. To establish the connection between the hippocampus and the locomotor system, electrical stimulation in the CA1 region was applied and EMG recordings were obtained. We also evaluated the hindlimbs and forelimbs kinematic patterns in rats with a penetrating injury (PI) in the hippocampus as well as in a cortex-injured group (CI), which served as control. After the PI, tamoxifen a selective estrogen receptor modulator (SERM) that has been described as a neuroprotector and antiinflammatory drug, or vehicle was administered. Electrical stimulation in the hippocampus produces muscle contractions in the contralateral triceps, when 6 Hz or 8 Hz pulse trains were applied. The penetrating injury in the hippocampus reduced the EMG amplitude after the electrical stimulation. At 7DPI (days post-injury) we observed an increase in the strides speed in all four limbs of the non-treated group, decreasing the correlation percentage of the studied joints. After 15DPI the strides speed in the non-treated returned to normal. These changes did not occur in the tamoxifen group nor in cortex-injured group. After 30 days, the nontreated group presented a reduction in the number of pyramidal cell layer neurons at the injury site, in comparison to the tam-treated group. The loss of neurons, may cause the interruption of the trisynaptic circuit and changes in the locomotion speed. Tamoxifen preserves the pyramidal neurons after the injury, probably resulting in the strides speed recovery.